Ball Recovery Consistency as a Performance Indicator in Elite Soccer - Mohammad Maleki; Kourosh Dadkhah; Farhad Alahvisi (Universidade Federal de Santa Catarina, 2016)
In soccer, an attack begins with ball recovery. Therefore, the consistency of this performance indicator during a match and its balanced distribution in the field zones can be one of the distinct characteristics of successful soccer teams. This study aims to investigate the performance consistency of ball recovery during a match within several time periods (6 periods of 15 min) and zones (four zones). To this end, observational methodology and software Focus X2 were adopted to evaluate 28 matches of semi-final teams at FIFA 2014 including Germany, Argentina, Netherlands, and Brazil in terms of ball recovery frequency. In total, 3222 performances were recorded. All teams in each match and in whole competition had homogeneity of distribution of ball recovery during the time periods (χ2 3=1.597, p=0.66). The results of time-zone evaluation indicated that Netherlands and Brazil teams did not have performance consistency on all field zones (χ2 15=31.29, p=0.008 and χ2 15=37.53, p=0.001, respectively). Most ball recoveries were made in the defensive and middle-defensive zones in accordance with modern soccer. It was found that for a soccer team to be successful, it requires a space distribution of experienced players in the field, which leads to power balance for redesigning a team to be offensive in all zones.